Perbandingan Pengencer Andromed, Susu Skim dan Pengencer Alami Terhadap Kualitas Spermatozoa Sapi Bali (Bos sondaicus) - Mardiana, Mardiana (bionature, 2017)
Abstract. The purpose of this study is to describe the effect of natural and synthetic based diluents in maintaining the quality of Balinese cement semen during storage in temperatures of 4-50Â°C. This research was conducted at UPTD IB (Technical Implementation Unit of Artificial Insemination Service), Pucak Village, Tompobulu Subdistrict, Maros Regency, South Sulawesi. This study was an experimental study using a complete randomized design (RAL) with 4 treatments namely Andromed diluents, Skim milk + egg yolks, Coconut Water + egg yolk and Honey + egg yolk with three replications. The data obtained in the form of sperm motility was analyzed using ANOVA and continued with Duncan test. The results showed that the motility of spermatozoa in the Andromed diluent was significantly different from the other three diluents: skim-yolk, coconutyolk and honey + yolk. The highest motility of spermatozoa on storage in the andromed diluent (50.00%) followed by spermatozoa in diluent Honey + egg yolk at concentration of 5% (50,00) skim-yellow egg (40.00%) and coconut water yolk (45.00%) at hour 0 while at 8th hour the highest motility on storage in andromed diluents (45.00%) followed by spermatozoa in diluent Honey + egg yolks (36,00) skim-yolk 31.00%) and yellow coconut water solvent (25.00%) this occurs because of the length of storage and the occurrence of cold shock effect that resulted in many dead spermatozoa. Keywords: dilution balinese cattle, andromed, skim milk, honey, coconut water, and egg yolk.